2014
DOI: 10.1007/s10409-014-0073-2
|View full text |Cite
|
Sign up to set email alerts
|

An experimental research on surface oscillation of buoyant-thermocapillary convection in open cylindrical annuli

Abstract: An experiment is carried out on the surface oscillation of buoyant-thermocapillary convection in an open cylindrical annulus. When the radial temperature difference ΔT reaches a critical value ΔT c , a regular oscillation appears and soon disappears on the open surface, which varies when the liquid layer's thickness h and temperature difference ΔT are varied. With growth of ΔT , dominant frequency of the visible oscillation will grow too but is found within certain frequencies. Driving forces, buoyance and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…As the thermal motion in the pool continues to accelerate, the frequency can be expressed as a function of Ma. In figure 11, Ma for various Vr shows a monotonically increasing behaviour, which is in good agreement with the ground experimental result (Zhang et al 2014). The linear fitting slope of the frequency with the variable is in the range 0.001-0.002, and there is no notable difference between the results of different volume ratios.…”
Section: Critical Temperature Difference and Frequencysupporting
confidence: 86%
See 3 more Smart Citations
“…As the thermal motion in the pool continues to accelerate, the frequency can be expressed as a function of Ma. In figure 11, Ma for various Vr shows a monotonically increasing behaviour, which is in good agreement with the ground experimental result (Zhang et al 2014). The linear fitting slope of the frequency with the variable is in the range 0.001-0.002, and there is no notable difference between the results of different volume ratios.…”
Section: Critical Temperature Difference and Frequencysupporting
confidence: 86%
“…The volume ratio also seriously affects the critical temperature difference, frequency, wavenumber, etc., exhibiting nonlinearity in their relationships. It has been confirmed that the frequency and wavenumber are much smaller than those of terrestrial experiment results (Zhang et al 2014). The wavenumber in space no longer decreases as the liquid layer thickens (Schwabe 2002;Schwabe & Benz 2002), but decreasing first, then increasing and finally decreasing, which is influenced by the flow state.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…The investigation of thermocapillary flow is important for basic research, as well as for material sciences, chemical engineering, and space manufacturing (Zhu et al 2011;Zhang et al 2014). When the gravity effect is greatly reduced, the interfacial phenomenon becomes important.…”
Section: Introductionmentioning
confidence: 99%